Individual Preparedness and Response to Chemical, Radiological, Nuclear, and Biological Terrorist Attacks - Davis, Lynn E.; Melmed, Arthur; Krop, Richard (RAND Corporation, 2023)
Individual preparedness is an important element of our nation's strategy for homeland security. This report adopts a scenario-driven approach that provides a rigorous way to identify actions-linked specifically to terrorist attacks-individuals can take to protect their health and safety. The result is an individual's strategy across four types of terrorist attacks-chemical, radiological, nuclear, and biological-consisting of overarching goals and simple and directive response and preparatory actions. The actions are appropriate regardless of likelihood of an attack, scale of attack, or government alert level; designed to be sensitive to potential variations; and defined in terms of simple rules that should be easy for individuals to adopt.